Comparative Adhesion of Pseudomonas aeruginosa to Human Oral Mucosal Epithelial Cells and Polystyrene Surfaces - Talib, Marwa M.; Ghafil, Jenan A. (Journal of the Faculty of Medicine Baghdad, 2024)
Background: The adhesion of bacteria to biotic and abiotic surfaces reflects their ability to cause infectious diseases. The distinction between the ability of Pseudomonas aeruginosa bacteria to adhere to biotic and abiotic surfaces is not clear in the literature.Objectives: The current study aims to shed light on the extent of similarities and differences between P. aeruginosa in terms of their ability to adhere to different biotic and abiotic surfaces.Materials and Methods: ten isolates of P. aeruginosa were isolated from 100 wound and burn swabs. The isolates were identified using biochemical and phenotypic tests in addition to VITIK-II technology. The susceptibility to antibiotics was estimated using the disc diffusion method. The microtiter-spectrophotometric was used to measure the biofilm formation on polystyrene microtiter plates. The Human oral mucosal epithelial (OMECs) were used to evaluate the adhesion of P. aeruginosa isolates. Plate count and direct bacterial count were used to count the adhered bacteria to human OMECs in vitro.Results: Norfloxacin showed the highest antibacterial effect while the lowest antibacterial effect was seen in the case of using when Amoxicillin and Cefixime (all isolates were resistant). All isolates from, Pa2 form the highest biofilm followed by Pa6, while the lowest biofilm formation was seen in the case of Pa4. While Pa 6 showed the highest ability to attach to human OMECs followed by Pa2.Conclusion: It can be concluded that P. aeruginosa isolates are resistant to most antibiotics and that their ability to adhere and biofilm formation depends on the type of surface.